THE COMPARATIVE BEHAVIOR OF MAMMALIAN EGGS IN VIVO AND IN VITRO : I. THE ACTIVATION OF OVARIAN EGGS - Pincus, Gregory (The Rockefeller University Press, 1935)
1. A definite chronological sequence of events occurs in the eggs and follicles of rabbits after mating or after the injection of ovulation-inducing substances. The follicle secretes secondary liquor folliculi, and there occurs a separation of the corona radiata from strands connecting it to the follicle cells. The ovum goes through nuclear maturation with as climax the production of the first polar body by the 8th hour after copulation. 2. Thyroxin injections cause indirectly the same effects as mating or pituitary injections but no ovulation occurs. The thyroxin effect occurs later than the pituitary effect and is due to an initiation of atresia in the follicles. 3. Explantation of ova results in typical maturation phenomena which are apparently unaffected by the presence of pituitary hormones or of thyroxin in the culture medium. 4. It is concluded that maturation of the ovum can be obtained simply by isolating it from the normal follicular environment. 5. Normal fertilization can be secured with eggs removed from the follicles.